The Interaction of Persona, Shadow, and Collective Unconscious in The Short Story of “Harta Ghoib” - Amalia, Dina; Nayla Nurbani Hawa; Mimin Zakiyah; Nur Leli; Rusli (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research aims to reveal the psychological condition of characters and society in the short story